Influence of electron-beam irradiation on thermal stabilization process of polyacrylonitrile fibers - Park, Mira; Choi, Yuri; Lee, Seul-Yi; Kim, Hak-Yong; Park, Soo-Jin (Journal of industrial and engineering chemistry (Seoul, Korea), 2014)
In this work, we prepared polyacrylonitrile (PAN)-based fibers treated with different doses of electron (E)-beam irradiation during the oxidative stabilization process to investigate the effect on their thermal behaviors and molecular structures. FT-IR and UV–vis absorption spectra of the E-beam irradiated PAN fibers show varying conjugation and transformation of CN to CN groups as a function of the dose. The thermal properties were characterized using differential scanning calorimetry and thermogravimetric analysis. E-beam irradiation lowers the onset temperature, extends the exothermic reaction, and improves the thermal stabilization. From these results, it is concluded that E-beam irradiation improves the thermal properties of PAN fibers as a result of cyclization of PAN molecules.